Aesthetic Perspectives in Romanian Theatre at the End of the First World War - CAZABAN, Ion (Studia Universitatis Babeș-Bolyai Dramatica, 2018)
The years 1919-1921 were years of nostalgia and imperative claims for the Romanian stage, years of useful comparisons with the achievements of the theatrical movements from other countries, of explorations in search for the best solutions, of enthusiastic impetuses and efforts to reach lucidity. This paper looks at the main issues and aesthetic ideas that were manifest during the controversies provoked by the premieres of several important theatrical productions within the above mentioned length of time. It also looks at the initiatives of certain cultural associations and at the discussions concerning the modern expressiveness of theatre and the creative role of the theatre director. Special consideration is given to the program and achievements of the National Theatre from Bucharest during the short period when it was led by the writer Victor Eftimiu.